Les représentations des étudiants de la formation BTS en Guadeloupe à l’épreuve des stages professionnels - Elisabeth Odacre; Elisabeth Issaieva; Antoine Delcroix (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This study concerns the functioning of some French BTS (Brevet de Technicien Supérieur / Advanced Technician Certificate), a professional diploma prepared in two years after the « baccalauréat », with national programs and evaluation criteria. The successful candidates are supposed to be immediately employable, especially in their local geographical environment, this can lead to tensions, as the program cannot be adapted to the different contexts. The professional training sessions in companies plays a great part in this diploma. We investigate how the representations of the students evolve with respect to the aforementioned paradox, during and after professional training sessions in companies. A longitudinal survey using questionnaire surveys was conducted with a cohort of the BTS tourism and deputy manager. In BTS tourism, the students remain attached to the aimed business sector, by questioning on the possibility of working in Guadeloupe while in BTS deputy manager, a degradation of the representation of the aimed job is noticed. The professional traineeship leads to a better understanding of the local economic situation and consequently modifies the representation of students.